The influence of burden and discipline of medical record personnel on performance and work motivation in hospitals - Laelani, Sofi Nur Eka April; Ramadhan, Yanuar; Hilmy, Mohammad Reza; Kusumapradja, Rokiah; Nofierni, Nofierni (Science Midwifery, 2024)
Background: In the process of achieving good employee performance, of course there are several factors that can influence it. From the results of observations and interviews conducted by the author, there are several problems that are indicated related to the performance of outpatient medical records personnel at Berkah Pandeglang Regional Hospital. This problem is one of the triggers for the low performance of medical records personnel. Performance-related problems encountered in hospitals include workload, work discipline, knowledge, leadership style and motivation. Aims: to determine the factors related to workload, work discipline and work motivation of medical record personnel on the performance of medical record personnel. Methods: This research is quantitative observational research. The population in this study was all 52 medical records employees. The sampling technique in this research is total sampling, where the sample taken is the same as the population. The sampling technique in this research is total sampling, where the sample taken is the same as the population. Results: Based on the results of the Sobel test, the significance value of the Work Load (X1) – work motivation (Z) – performance of Medical Record Personnel (Y) path is 0.007 < 0.05 with a calculated T value of 2.353 > 1.675, it concluded that work motivation is able to mediate the relationship between workload and the performance of Medical Records Personnel. Conclusion: Based on the results, it shows that work motivation can significantly mediate the influence of workload and work discipline on the performance variables of medical record personnel.